Kebumen Adhi Tagguh Mandiri (KATAM) Program Pengabdian Kepada Masyarakat Kewirausahaan Desa Berbasis Digital - Evi Rosalina Widyayanti; Suci Utami Wikaningtya; Ary Sutrischastini; Lilik Ambarwati; Anggie Febriyanti (LP3M Universitas Putra Bangsa, 2025)
The community of Grujugan Village, Petanahan District, Kebumen Regency, has a high interest in Entrepreneurship. However, this village faces various problems in aspects of Entrepreneurship, in general, and Digital Entrepreneurship, in particular. Therefore, Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha partnered with Grujugan Village to organize the KATAM Program, with the theme